Addressing challenges for operating electrochemical solar fuels technologies under variable and diurnal conditions - Yap, Kyra M. K.; Lee, Sol A.; Kistler, Tobias A.; Collins, Darci K.; Warren, Emily L.; Atwater, Harry A.; Jaramillo, Thomas F.; Xiang, Chengxiang; Nielander, Adam C. (Frontiers in Energy Research, 2024)
The outdoor operation of electrochemical solar fuels devices must contend with challenges presented by variations in the cycles of solar irradiance, temperature, and other meteorological factors. In this perspective, we discuss challenges associated with these fluctuations presented over three timescales, including the effects of diurnal cycling over the course of many days, a single diurnal cycle over the course of hours, and meteorological phenomena that cause fluctuations on the order of seconds to minutes. We also highlight both reaction-independent and reaction-specific effects of variable conditions for the hydrogen evolution reaction and CO2 reduction reaction. We identify key areas of research for advancing the outdoor operation of solar fuels technology and highlight the need for metrics and benchmarks to enable the comparison of diurnal studies across systems and geographical locations.